2017
DOI: 10.15344/2456-8171/2017/121
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Usage Related to Dietary Supplements in a Group of Canadian Dental Students: A Pilot Study

Abstract: Background: Considering the increasing usage of dietary supplements by the general population, knowledgeable dental practitioners should be able to guide patients concerning the judicial use, efficacy, adverse effects and potential drug interactions of these products. The aim of this study was to determine usage, knowledge, and attitudes related to dietary supplements in a group of Canadian dental students. Methods: A total of 105 dental students completed a questionnaire consisting of three parts; Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Based on study conducted in prince Naurah Bint Abdul rahaman University in Riyadh, Saudi Arabia, participants reported that taking supplements for mainly aesthetic reasons (45.6%), such as improving their skin and hair second common reason was health improvement and increased immunity (42.4%) (AlTamimi, 2019). considering research conducted among dental students in Canada, it also proved that most participants took supplements to maintain good health (65%) and to ensure proper nutrition (58 %) (Hoover, et al, 2017). In our study denoted that common reason for using dietary supplement was supply nutrients to the body 91.20% followed by, beauty benefits (81.90%), weight loss (77%), improvements to health (74.30%), prevention of diseases (69.90%) and maintenance of health (66.40%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on study conducted in prince Naurah Bint Abdul rahaman University in Riyadh, Saudi Arabia, participants reported that taking supplements for mainly aesthetic reasons (45.6%), such as improving their skin and hair second common reason was health improvement and increased immunity (42.4%) (AlTamimi, 2019). considering research conducted among dental students in Canada, it also proved that most participants took supplements to maintain good health (65%) and to ensure proper nutrition (58 %) (Hoover, et al, 2017). In our study denoted that common reason for using dietary supplement was supply nutrients to the body 91.20% followed by, beauty benefits (81.90%), weight loss (77%), improvements to health (74.30%), prevention of diseases (69.90%) and maintenance of health (66.40%).…”
Section: Discussionmentioning
confidence: 99%
“…Only 10.2% of participants are looking forward to the guidance of health care professionals when consuming dietary supplements. When considering with the Canadian study done in 2017 (Hoover, et al, 2017) it stated that approximately 39% of participants seek professional advice when consuming dietary supplements.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Ceschini et al (2022), 29.3% of adolescents in the municipality of Brazil were found to consume VMS without any professional guidance (self-prescription). Additionally, a vast number of current findings highlighted that no matter whether adults or adolescents, the reason they consumed dietary supplements is to maintain and improve their overall health level, also to prevent diseases (Cebula et al, 2018;Elsahoryi et al, 2023;Perlitz et al, 2019;Shahzad et al, 2022;Sicinska et al, 2022;Yazid et al, 202) as they believed that supplements help achieve their recommended nutrient intake (Hoover et al, 2017). This phenomenon was termed 'dietary insurance' (Whitney & Rolfes, 2018), whereby the concept is to improve the poor diet by simply taking a dietary supplement to 'cover up' poor dietary choices and is common among people who feel unsure about the nutritional adequacy of their diet.…”
Section: Introductionmentioning
confidence: 99%